Tinjauan Hasil Inseminasi Buatan Berdasarkan Anestrus Pasca Inseminasi Pada Peternakan Rakyat Sapi Bali Di Kabupaten Sikka Nusa Tenggara Timur - Tophianong, Tarsisius Considus (Fakultas Kedokteran Hewan UGM, 2014)
Anestrus is one of indirect clinical signs of cattle pregnancy. Based on the present of suffrcient progesterone on the blood, the caftle with pregnancy condition will not show the signs of estrus. The success of artificial insemination (AI) is the occurrence of fertilization followed by pregnancy and parrurition. This involves a complex relationship between semen quality and oocytes, estrus detection, AI punctuality, inseminator and farmers ability. Artificial insemination should be performed at the relative optimum time to ovulation. Estrus detection is an important factor to determine the time ofAI. Estrus detection of Bali cattles of the farmer is oft6n difficult observed or not obsen ed, especially in semi-intensive system maintenance. From this review it can be seen that there is the different proportion of inseminators on the incidence of estrus afterAI. However, determination of the role of inseminator on the success ofAI and then the other factors that affect the success of theAI should be under ideal conditions. Straw from the different bulls breed gave the same of AI result. The estimate of pregnancy rate of 80 cows after AI is 55 %. Estrus detection on 2 l " days after AI can be used as a detection method for early diagnosis of pregnancy, especially for the farmers who did not have any ability or authority to perform medical acts of reproduction which is only owned by a veterinarian. Observation, recording and evaluation of the implementation of theAI should be made until the end ofpregnancy followed by the process of parnirition.